Penjadwalan Perawatan Komponen Pada Sistem Pendingin Main engine Crew Boat 41 GT - Andreas Nova; Tasya Putri Lindyawati; Nurvita Arumsari; Aminatus Sa'diyah (Politeknik Perkapalan Negeri Surabaya, 2023)
Currently, there is a growing trend of damages occurring to the main engine, with some cases leading to sailing delays or even endangering human safety. The Crew Boat 41 GT is a vessel operating to transport crews or provide offshore support. Therefore, it is crucial to pay attention to the maintenance of its main engine, especially the cooling sub-system, which plays a vital role in maintaining the working temperature of the main engine to prevent overheating. Consequently, a suitable maintenance scheduling strategy is required for the sub-system components of the Crew Boat 41 GT's main engine to ensure the operational efficiency of the main engine is not disrupted. This study aims to predict the reliability using both qualitative (FMEA) and quantitative methods (theoretical and Monte Carlo simulation) to develop a plan for preventive maintenance scheduling, FMEA analysis identified three critical components, there are sea water pump, heat exchanger, and fresh water pump. The results of the quantitative analysis for these three critical components showed that the RLLM = 0.6, with little difference between the two methods. Additionally, error calculations were performed using RMSE, MAPE, and MAE, with results close to 0. Moreover, from the evaluation of corrective and preventive maintenance, it was found that preventive maintenance is more recommended as it can save costs by approximately 16.26% or Rp 7,703,292.56 for a single maintenance of all components.